Political economy and language education - M. Maksud Ali (Australian Review of Applied Linguistics, 2026)
Abstract Contemporary political economy has redefined relationships between most nation-states and citizens based on neoliberalism, whereby individuals’ dependency on the state is minimised and self-reliance is emphasised. How such a framing of the relationships relates to language education policy has not received notable attention in developing societies. Using a political economy frame and drawing on Bourdieu’s concept of field and his analytical framework of field analysis, together with Lingard and Rawolle’s theory of cross-field effects , this study conducted policy analysis to theorise how these emerging relationships provide the basis for the economisation of English language education in Bangladesh. The analysis highlights how an economistic logic emphasised in public policy governs language education in relation to a logic of relevance . In the context of political economy in language education, these insights provide new theoretical directions to understand the processes through which language education is economised via cross-field effects. The study generates implications for interrogating how language education goals are instrumentalised vis-à-vis pressures from structurally dominant social fields, and how unequal linguistic human capital distribution may be encouraged by how state-people relationships are defined in the field of public policy based on the principle of individualisation.